Peranan E-Commerce dalam Meningkatkan Daya Saing Keuangan Inklusif UMKM di Kabupaten Kudus yang Berbasis Fintech - Zuliyati Zuliyati; Wiwit Agus Triyanto; Retno Tri Handayani (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2021)
Online-based trading changes the traditional trading paradigm, through meetings between consumers and merchants turning into online transactions without distance and time limits. E-commerce changes MSME to trade online by utilizing the internet and the web, so that e-commerce makes the buying and selling process not hindered by distance and time. This change has led to the emergence of Fintech (Financial Technology). Many MSME have gone out of business because they cannot compete with MSME that can take advantage of technology in managing their businesses. This study aims to analyze the effect of e-commerce on fintech-based financial management at MSME in Kudus Regency, so it is hoped that e-commerce will have a role in increasing the competitiveness of fintechbased financial inclusion in Kudus Regency. The population used is the MSME in Kudus district. The sample selection using the purposive sampling technique with the criteria for MSME who are members of the shopee community. This study uses linear regression analysis.Keywords: Fintech, E-commerce, MSME Perdagangan berbasis online mengubah paradigma perdagangan tradisional, melalui pertemuan antara konsumen dan pedagang berubah menjadi transaksi online tanpa batas jarak dan waktu. E-commerce mengubah UMKM untuk melakukan perdagangan secara online dengan memanfaatkan internet dan web, sehingga e-commerce menjadikan proses jual beli tidak terhalang jarak dan waktu. Perubahan inilah yang mendorong munculnya Fintech (Financial Technologi). Banyak UMKM gulung tikar karena kalah bersaing dengan UMKM yang bisa memanfaatkan teknologi dalam mengelola bisnisnya. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh e-commerce terhadap pengelolaan keuangan berbasis fintech pada UMKM di Kabupaten Kudus, sehingga diharapkan e-commerce mempunyai peranan dalam meningkatkan daya saing keuangan inklusif UMKM di Kabupaten Kudus berbasis fintech. Populasi yang digunakan adalah UMKM pelaku e-commerce di kabupaten Kudus dengan pemilihan sampel menggunakan metode Teknik purposive sampling dengan kriteria UMKM yang tergabung dalam komunitas shopee. Penelitian ini menggunakan analisis regresi linier sederhana.Keywords: Fintech, E-commerce, UMKM